IMPROVING STUDENTS' ABILITY IN SPEAKING OF PROCEDURAL TEXT WITH BALABOLKA ('TEXT TO SPEECH') - Titis Pawiyati RP Pramono (ELite Journal : International Journal of Education, Language, and Literature, 2022)
This classroom action research is an effort to describe the impact of using 'Balabolka Text to speech' to raise the students' skill to produce Oral Procedural Text, especially about the Manual and Tips. It is one of the solutions to rid of the difficulties of English teachers in handling the students' oral learning activity. A test was given to 36 students of Class XI in a senior high school in Sidoarjo that have already applied Balabolka Text to Speech to learn about the Manual and Tips of Procedural Text. The function of this application is to convert any written texts into audio files, which can be used to train the students' skills in speaking about the steps to demonstrate manual and tips. The prospective advantages of the qualitative approach show that the usage of Balabolka Text to Speech in the English classroom may increase the students' skills to understand the oral Manual and Tips of Procedural Text. It includes: (1) improving the students' ability to mention the communicative purpose, ingredients and/or tools, and the steps of performing it after using the application, (2) raising the students' speaking skills to comprehend the text by observing the effectivity of the application.